Lymphoma and Epstein−Barr virus DNA in blood during interleukin‐2 therapy in antiretroviral‐naïve HIV‐1‐infected patients: a substudy of the ANRS 119 trial. Issue 1 (6th September 2013) - de, V; LeGoff, J; Brière, J; Agbalika, F; Boulet, T; Lévy, Y; Simon, F; Aboulker, J‐P; Molina, J‐M
<x xml:space="preserve">Abstract</x> Objectives Interleukin‐2 (IL‐2) therapy increased CD4 cell counts and delayed antiretroviral therapy (ART) initiation in HIV‐infected patients in the Agence Nationale de Recherche sur le SIDA et les Hépatites Virales (ANRS) 119 trial. However, four cases of lymphoma were reported. Epstein−Barr virus (EBV) replication is associated with an increased risk of lymphoma in immunocompromised patients. We assessed whether IL‐2 had an impact on EBV replication and the development of lymphoma. Methods A total of 130 ART‐naïve patients were randomized to receive IL‐2 therapy (n = 66) or no treatment (n = 64). Clinical data for patients with lymphomas were reviewed and tumours assessed for evidence of EBV infection and CD25 (the IL‐2 receptor) expression. EBV DNA levels were measured in whole blood and plasma in both arms using real‐time polymerase chain reaction (PCR), up to 48 weeks after baseline (BL). Results Four lymphomas occurred, a median of 61 weeks [range 40−94 weeks] after randomization at a median CD4 cell count of 396 cells/μL (IQR 234–536 cells/μL). In the IL‐2 arm, two patients developed EBV‐positive Hodgkin's lymphoma, and one developed EBV‐negative Burkitt‐type lymphoma. One patient in the control group developed EBV‐positive non‐Hodgkin's lymphoma. CD25 was negative in all cases. Among the 41 of 55 (control arm) and 44 of 58 (IL‐2 arm) patients with detectable EBV DNA in whole blood at both BL and week 48, the median change in EBV DNA between BL and week 48 was +0.04 log10 copies/ml in both arms (P = 0.7). In plasma, EBV was detected at least once in 22 of 52 controls and 21 of 54 IL‐2‐treated patients (P = 0.8). Conclusions IL‐2 therapy had no significant effect on EBV replication over 48 weeks in these ART‐naïve patients. The occurrence of lymphomas did not seem to be associated with IL‐2 therapy.